Food-borne microbes : shaping the host ecosystem - Jaykus, Lee-Ann.; Wang, Hua H. (Hua Helen), 1965-; Schlesinger, Larry S. (Washington, D.C. : ASM Press, 2009)
With contributions from experts in environmental, food, oral, medical, and veterinary microbiology, this book takes an interdisciplinary approach that sheds new light on microbial communities and their interactions within and between different environments, with an emphasis on food systems. The book underscores the role played by food and food-borne microbes in host ecosystem development by connecting complex ecosystems from the environment to the host and linking them to the food carrier.
The oral microbial ecosystem and beyond / Howard F. Jenkinson and Richard J. Lamont -- The gut microbiome : current understanding and future perspectives / Zhongtang Yu and Mark Morrison -- Natural microbial ecosystems and their progression in fresh foods / James M. Jay -- Microbial succession and gut health : probiotics / Gerald W. Tannock -- Interactions between environmental microbial ecosystems and humans : the case of the water environment and antibiotic resistance / Chuanwu Xi [and others] -- Biofilms in the food environment / Joseph F. Frank -- Quorum sensing and signal transduction in biofilms : the impacts of bacterial social behavior on biofilm ecology / Yung-Hua Li -- Molecular mechanisms of microbial survival in foods / Francisco Diez-Gonzalez and Julie Kuruc -- Using microbial succession to the processor's advantage : food fermentation and biocontrol / Trevor G. Phister -- The interaction of bile salts with pathogenic and nonpathogenic intestinal bacteria / Robert W. Crawford and John S. Gunn -- The influence of helminths on immunological diseases / Joel V. Weinstock and David M. Elliott -- The evolution of antibiotic-resistant microbes in foods and host ecosystems / Marilyn C. Roberts -- Antimicrobial resistance in food-borne pathogens / David G. White and Patrick F. McDermott -- Commensal bacteria, microbial ecosystems, and horizontal gene transmission : adjusting our focus for strategic breakthroughs against antibiotic resistance / Hua H. Wang -- Antibiotic resistance and the fitness of enteric pathogens / Qijing Zhang and Dan I. Andersson -- Staphylococcus aureus : the "superbug" / Michael Otto -- Mycobacterium avium subsp. paratuberculosis : an unconventional pathogen? / Srinand Sreevatsan, Natalia Cernicchiaro, and Radhey Kaushik -- Molecular methods to study complex microbial communities / Dionysios A. Antonopoulos [and others] -- Mathematical modeling of microbial ecology: spatial dynamics of interactions in biofilms and guts / Jan-Ulrich Kreft.
Includes bibliographical references and index.
Keywords: Food -- Microbiology; Microbial ecology; Gastrointestinal system -- Microbiology